POST-TRANSPLANT FUNCTIONAL STATUS TRAJECTORY AMONG ADULT KIDNEY TRANSPLANT RECIPIENTS. (8th November 2019) - Chu, Nadia M; Shi, Zhan; Haugen, Christine; Segev, Dorry; McAdams-DeMarco, Mara
Abstract: Frailty and disabilities are highly prevalent among kidney transplant (KT) recipients, but are not routinely measured in KT recipients. The Karnofsky Performance Scale (KPS) is a clinically perceived measure used to evaluate patient's ability to manage daily activities, but little is known about its post-KT trajectories and its relationship to frailty and disability in KT recipients. We leveraged a cohort of 159, 992 adult KT recipients from SRTR (1/2005-6/2018) and a cohort of 1, 106 adult KT recipients from a prospective cohort study on aging and KT with recorded KPS (range 10%-100% integers). In each separate cohort, we used mixed effects models to assess differences in trajectories of KPS post-KT. In 159, 992 KT recipients in SRTR, the mean unadjusted KPS score was 88.34% (95%CI: 88.28%, 88.40%) and declined at a rate of -0.59%/year (95%CI: -0.61%, -0.57%) post-KT, such that by 2-years post-KT the average was 87.00% (95%CI: 86.94%, 87.05%). Age at KT was associated with steeper decline in KPS (p0.05). KPS is a measure of functional status distinct from frailty, ADL, IADL, and SPPB at KT admission that declines with older age post-KT. Older KT recipients should be monitored closely for declines in physical function, and potentially undergo prehabilitation to improve functional status post-KT.